2015
DOI: 10.1371/journal.pone.0115039
|View full text |Cite
|
Sign up to set email alerts
|

Sectorial Water Use Trends in the Urbanizing Pearl River Delta, China

Abstract: Assessing and managing water use is crucial for supporting sustainable river basin management and regional development. The first consistent and comprehensive assessment of sectorial water use in the Pearl River Delta (PRD) is presented by analysing homogenized annual water use data from 2000 to 2010 in relation to socio economic statistics for the same period. An abstraction of water use, using the concept of water use intensity, and based on equations inspired by those used in global water resource models, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…Chen (2006a) concludes that the water management system in the PRD neglects managing the water uses because the PRD is a water abundant region. In previous work, I confirm that on annual time scales the PRD has enough water supplies to fulfil its water use2 (Yao et al 2015). Nevertheless, seasonal water shortages have occurred due to the severe salt intrusion.…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…Chen (2006a) concludes that the water management system in the PRD neglects managing the water uses because the PRD is a water abundant region. In previous work, I confirm that on annual time scales the PRD has enough water supplies to fulfil its water use2 (Yao et al 2015). Nevertheless, seasonal water shortages have occurred due to the severe salt intrusion.…”
Section: Introductionsupporting
confidence: 60%
“…To obtain consistent trends of sectorial water uses during the study period, data homogenization as reported by Yao et al (2015) was also applied here. …”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations